The potential of chronopharmacology for treatment of atherosclerosis. Issue 5 (October 2018) - Winter, Carla; Soehnlein, Oliver
Abstract : Purpose of review: Development of atherosclerosis contributes to cardiovascular diseases that still are the leading cause of mortality worldwide. Successful strategies for treating inflammatory aspects of atherosclerotic lesion development are rare. Here, we review new insights into the impact of circadian rhythmicity on atherogenesis and their potential for innovative time-optimized pharmacological treatment strategies. Recent findings: Studies on the circadian clock revealed an extensive influence on immune cell activity. Immune cell functionality and their recruitment to injured tissues exhibit circadian rhythmicity. Many indications that the circadian clock also modulates atherogenesis were given in the past. Transcriptome analysis of the aorta reveals a time-dependent expression profile. Furthermore, deficiency of the core clock proteins Bmal1 and Clock consistently accelerates atherosclerosis. Recent work provided new insights on time-dependent leukocyte recruitment to atherosclerotic lesions and its regulatory mechanisms through the CCR2-CCL2 axis. Based on timed CCR2-CCL2 signaling blockage, an effective chronopharmacological treatment strategy was established to reduce early lesion development with concomitant reduction of systemic side effects. Summary: Circadian rhythmicity impacts on the pathogenesis of atherosclerosis. Circadian oscillation in the expression of drug targets may license timed intervention strategies with improved efficacy and lower risk.